2007
DOI: 10.1098/rspb.2007.1043
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection explains Rensch's rule of allometry for sexual size dimorphism

Abstract: In 1950, Rensch first described that in groups of related species, sexual size dimorphism is more pronounced in larger species. This widespread and fundamental allometric relationship is now commonly referred to as 'Rensch's rule'. However, despite numerous recent studies, we still do not have a general explanation for this allometry. Here we report that patterns of allometry in over 5300 bird species demonstrate that Rensch's rule is driven by a correlated evolutionary change in females to directional sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
209
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(221 citation statements)
references
References 40 publications
7
209
1
4
Order By: Relevance
“…For each population, body size was defined as mean female wing length 52 , either for individuals measured at the breeding area or at the wintering area. In case no individuals were measured, we used the mean value from the literature (see open access data for specific values and references 53 ).…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…For each population, body size was defined as mean female wing length 52 , either for individuals measured at the breeding area or at the wintering area. In case no individuals were measured, we used the mean value from the literature (see open access data for specific values and references 53 ).…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…Allometry consistent with Rensch's Rule has been confirmed in a range of avian taxa, but significant examples are generally associated with male-biased SSD, suggesting that sexual selection acting on male size drives the evolution of this pattern of allometry [32]. Although Rensch's Rule has also been demonstrated in Charadriiformes [33], other studies have found no evidence for it in Falconiformes, Strigiformes or Tinamiformes, suggesting that it is not generally supported in birds that exclusively exhibit RSD [3,28].…”
Section: Introductionmentioning
confidence: 80%
“…Esto se debe a varios factores entre los que figura en forma prominente el hecho de que ninguno de los mecanismos evolutivos propuestos para explicar el escalamiento de SSD con el tamaño corporal, resulta satisfactorio. Habitualmente, se ha considerado a la selección sexual como el factor predominante detrás del escalamiento entre el SSD y el tamaño corporal (Hedrick y Temeles 1989;Fairbairn 1997Fairbairn , 2005Székely et al 2004;Dale et al 2007;Lindenfors et al 2007). El SSD puede ser explicado de forma relativamente simple por la selección sexual (Maynard Smith 1982Reiss 1989) sin embargo, la relación alométrica entre SSD y tamaño requiere una mayor variabilidad en tamaño en machos, y una respuesta diferencial a la selección de tamaño corporal en machos y hembras aún cuando ambos sexos comparten la mayor parte de los genes responsables por este carácter (Fairbairn 1997).…”
Section: Discussionunclassified
“…A partir de la publicación de "The Descent of Man and Selection in Relation to Sex" por Darwin (1871), el SSD ha sido considerado esencialmente como producto de la acción de la selección sexual en el sentido darwiniano de competición intrasexual por el acceso a la pareja en uno de los sexos, y la elección o preferencia por parte del otro (Trivers 1972;Andersson 1994;Isaac 2005;Dale et al 2007). Sin embargo, la selección natural clásica también puede explicar el SSD si favoreciese diferentes tamaños corporales para adecuar los sexos a diferentes papeles ecológicos o de utilización de nicho, o si competencia alimentaria ocurre entre machos y hembras (Hedrick y Temeles 1989;Shine 1989;Andersson 1994;Mysterud 2000;Isaac 2005).…”
Section: Introductionunclassified